A Finger-Stick Whole-Blood HIV Self-Test as an HIV Screening Tool Adapted to the General Public - Prazuck, Thierry; Karon, Stephen; Gubavu, Camelia; Andre, Jerome; Legall, Jean Marie; Bouvet, Elisabeth; Kreplak, Georges; Teglas, Jean Paul; Pialoux, Gilles (PLOS ONE, 2016)
Background In 2013, the French Health Authority approved the use of HIV self-tests in pharmacies for the general public. This screening tool will allow an increase in the number of screenings and a reduction in the delay between infection and diagnosis, thus reducing the risk of further infections. We previously compared 5 HIV-self test candidates (4 oral fluid and one whole blood) and demonstrated that the whole blood HIV test exhibited the optimal level of performance (sensitivity/specificity). We studied the practicability of an easy-to-use finger-stick whole blood HIV self-test “autotest VIH®”, when used in the general public. Methods and Materials This multicenter cross-sectional study involved 411 participants from the Parisian region (AIDES and HF association) between April and July 2014 and was divided into 2 separate studies: one evaluating the capability of participants to obtain an interpretable result using only the information notice, and a second evaluating the interpretation of test results, using a provided chart. Results A total of 411 consenting participants, 264 in the first study and 147 in the second, were included. All participants were over 18 years of age. In the first study, 99.2% of the 264 participants correctly administered the auto-test, and 21.2% needed, upon their request, telephone assistance. Ninety-two percent of participants responded that the test was easy/very easy to perform, and 93.5% did not find any difficulty obtaining a sufficient good quantity of blood. In the second study, 98.1% of the 147 participants correctly interpreted the results. The reading/interpretation errors concerned the negative (2.1%) or the indeterminate (3.3%) auto-tests. Conclusions The success rate of handling and interpretation of this self-test is very satisfactory, demonstrating its potential for use by the general public and its utility to increase the number of opportunities to detect HIV patients.